Measuring the Impact of Mental Accounting on Financial and Investment Decisions among Investors - Rashwan, Abd El Rahman Mohammed; Shaqfa, Khalil Ibrahim (The Arab Journal of Administration, 2024)
The study aims to identify the impact of mental accounting on financial and investment decision-making among Palestinian investors. The study used the descriptive analytical method, and the study was based on a questionnaire distributed to the sample of the study consisting of (136) Palestinian investors, and the results of the study found that mental accounting contributes to enhancing the risk assessment of financial and investment decisions of Palestinian investors, thus avoiding the risks associated with the decisions taken, and recommended the need to conduct simulation models to raise the financial culture of investors in light of the uses of mental accounting in financial and investment decisions in order to increase the skills and potential of investors in managing the information available to them in the portfolio management Finance.